An evaluative study on the safety and comfort of postpartum mothers in the obstetrics service ward of Dr. Jose Fabella Memorial hospital - Gascon, Ciara-Mae T.; Brasileño, Lynne I. (Quezon City College of Home Economics, University of the Philippines Diliman, 2017)
This study evaluated the safety and comfort of postpartum mothers in the obstetrics service ward of Dr. Jose Fabella Memorial Hospital. The study aimed to determine the current condition of the obstetrics service ward and how it affected the physiological and psychological state of the postpartum mothers, as well as how they perceived their safety and comfort inside the ward. This study includes the postpartum mothers from the Obstetrics Ward IV of Dr. Jose Fabella Memorial Hospital. Cultural proxemics was used to evaluate the safety and comfort of postpartum mothers inside the hospital wards. Filipino values were also used as basis to examine concepts on cultural proxemics. The study is descriptive in nature, and it employed convenience sampling in selecting five 5 respondents and one 1 key informant. The tools used for data gathering were recording devices for the photo documentation, as well as temperature and sound level reading, an interview schedule, and a site inspection sheet. Generally, the postpartum mothers expressed their concerns with regard to the lack of privacy, limited space for movements, noise level, and the yellowish rendering caused by the lighting inside the ward. The results showed that the selected postpartum mothers were most comfortable with the people they can identify with, such as their fellow postpartum mothers and their babies, and there was a certain level of uneasiness when it came to their encounters with nurses and staff, especially the males. The limited space to move around was also observed. The lack of territories and their overlapping intimate spaces as well as their observance of Filipino values such as pakikipagkapwa-tao and family-orientedness, which emphasizes the value of smooth interpersonal relationships helped them adapt to their environment by coordinating with other mothers, and being sensitive to their needs. The space encouraged the mothers to interact, and the tandem beds facilitated a sharing of resources and knowledge among them. It is recommended to conduct further research on the respondents socio-economic status, since it may affect their perception of their safety and comfort inside the facility. A comparative study between government-owned and private hospitals may also be considered.
submitted June 2017
Thesis (B.S. Interior Design)--University of the Philippines Diliman.
Keywords: Hospital buildings -- Design and construction